2017
DOI: 10.1186/s13045-017-0401-7
|View full text |Cite
|
Sign up to set email alerts
|

Studying hematopoiesis using single-cell technologies

Abstract: Hematopoiesis is probably the best-understood stem cell differentiation system; hematopoietic stem cell (HSC) transplantation represents the most widely used regenerative therapy. The classical view of lineage hierarchy in hematopoiesis is built on cell type definition system by a group of cell surface markers. However, the traditional model is facing increasing challenges, as many classical cell types are proved to be heterogeneous. Recently, the developments of new technologies allow genome, transcriptome, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 121 publications
0
35
0
Order By: Relevance
“…Single-cell RNA sequencing has become a powerful tool to characterize distinct functional states at single-cell resolution [115][116][117]. Several studies using single-cell RNA sequencing have been performed to reveal cellintrinsic differences during HSC aging [22,25].…”
Section: Single Cell Technologies For Hsc Aging Single-cell Rna Sequementioning
confidence: 99%
See 1 more Smart Citation
“…Single-cell RNA sequencing has become a powerful tool to characterize distinct functional states at single-cell resolution [115][116][117]. Several studies using single-cell RNA sequencing have been performed to reveal cellintrinsic differences during HSC aging [22,25].…”
Section: Single Cell Technologies For Hsc Aging Single-cell Rna Sequementioning
confidence: 99%
“…The development of single-cell epigenomic technologies has allowed the identification of DNA methylation, histone modifications, chromatin accessibility, and chromosome conformation at the single-cell level [117,124]. For example, single-cell chromatin immunoprecipitation sequencing and single-cell assays for transposaseaccessible chromatin using sequencing (scATAC-seq) have been applied to investigate histone modifications and to map accessible chromatin regions.…”
Section: Epigenetics At the Single-cell Levelmentioning
confidence: 99%
“…Various hierarchical models for differentiation have been proposed (cf. Kawamoto, Wada, & Katsura, 2010;Ye, Huang, & Guo, 2017). The equal loss of potentials (ELP) model was introduced in Perié et al (2014), and is described next.…”
Section: Loss Of Potentials In Hematopoiesismentioning
confidence: 99%
“…However, several studies have revealed novel concepts regarding HSC homeostasis that are distinct from the classical hierarchy 10 . Recent studies using transcriptomic, proteomic, and epigenetic profiling of HSCs have revealed that HSC populations are heterogeneous 11 , and studies with additional indicators have demonstrated that even the LT-HSC population is heterogeneous 12 . Therefore, additional tools are required to further separate HSCs into their component populations.…”
Section: Introductionmentioning
confidence: 99%